The Impact of Cr3+ Doping on Temperature Sensitivity Modulation in Cr3+ Doped and Cr3+, Nd3+ Co-doped Y3Al5O12, Y3Al2Ga3O12, and Y3Ga5O12 Nanothermometers - Elzbieciak, Karolina; Marciniak, Lukasz (Frontiers in Chemistry, 2018)
A new approach to enhance the sensitivity of transition metal ion based nanocrystalline luminescent thermometer is presented. It was shown that the increase of Cr3+ concentration in three types of garnet host namely Y3Al5O12, Y3Ga5O12 and Y3Al2Ga3O12 allows for significant enhancement of their performance in non-contact thermometry. This phenomenon is related to the weakening of the crystal field strength due to enlargement of average Cr3+-O2- distance at higher Cr3+ concentrations. By increasing Cr3+ concentration from 0.6% to 30%, the sensitivity increased by over one order of magnitude from S=0.2%/oC to S=2.2%/oC at 9oC in Y3Al2Ga3O12 nanocrystals. Moreover, it was found that due to the Cr3+→Nd3+ energy transfer in the Cr3+, Nd3+ co-doped system, the usable Cr3+ concentration, for which its emission can be detected, is limited to 10% while the sensitivity at -50 oC was doubled (from 1.3%/oC for Y3Al2Ga3O12:10%Cr3+ to 2.2%/oC Y3Al2Ga3O12:10%Cr3+, 1%Nd3+ nanocrystals).